EKSPLORASI MIKROALGA DI SUNGAI MESAT KOTA LUBUKLINGGAU - Harmoko Harmoko; Merti Triyanti; Lukman Aziz (Universitas Sultan Ageng Tirtayasa, 2018)
The Mesat River is one of the rivers that cross the City of Lubuklinggau. Community activities around the river Mesat less maintain the river can disrupt the river ecosystem Mesat itself. The purpose of this study is to explore the microalgae in the Mesat River Lubuklinggau City. This research uses survey method, carried out on three stations with three repetitions in the waters of the Mesat River Kecamatan Lubuklinggau Timur II Lubuklinggau Town and identified in the Biology Laboratory STKIP-PGRI Lubuklinggau. Data were analyzed descriptively qualitative. The results of the study found microalgae in the Mesat River of Lubuklinggau City consisting of 4 Divisions, 6 Classes, 15 Orders, 19 Famili, 27 Genus and 32 Species. Mesi Abiotik Factor Measurement Results: mean temperature value 250C, average PH value 7.2, average brightness value 18.2 cm and Average Dissolved Oxygen Value 4.64 mg/L. Based on the results of this study it can be concluded that the type of microalgae found in the Mesat River consists of: Ankistrodesmus sp, Micrasterias radiata, Coelastrum sp, Zygnema sp, Chroococus sp, Xanthidium sp, Dictyosphaerium sp, Chlamydomonas sp, Carteria sp, Lyngbya sp, Rhizoclonium hieroglyphicum, Cylotella sp, Surirella elegans, Spyrogira sp, Eunothia sp, Gonatozygon sp Chlorella sp, Oscillatoria limosa, Oscillatoria sp, Tabellaria sp, Pediastrum singulex, Pediastrum duplex, Closterium sp, Cosmarium sp, Mougeotia sp, Phacus triqueter, Phacus lomgicauda, Euglena viridis, Euglena mutabilis, Scenedesmus sp, Scenedesmus acuminatus, and Scenedesmus opaliensis.